2021
DOI: 10.1097/moh.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis driven by DNMT3A and TET2 mutations: role in monocyte and macrophage biology and atherosclerotic cardiovascular disease

Abstract: Purpose of review Clonal hematopoiesis of indeterminate potential (CHIP), defined by the presence of somatic mutations in hematopoietic cells, is associated with advanced age and increased mortality due to cardiovascular disease. Gene mutations in DNMT3A and TET2 are the most frequently identified variants among patients with CHIP and provide selective advantage that spurs clonal expansion and myeloid skewing. Although DNMT3A and TET2 appear to have oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 71 publications
(100 reference statements)
1
26
0
Order By: Relevance
“…The high incidence of sub-clinical CHIP poses two key questions: First, how do lesions in epigenetic control mechanisms lead to persistent, low-level clonal expansion without causing overt transformation, and second, how can mutations in genes encoding such opposing activities as methylation ( DNMT3A ) and demethylation ( TET2 ) have such similar consequences? CHIP is associated with an increased risk of atherosclerotic cardiovascular disease [ 23 ] and this has led to the identification of de-regulated inflammation as a common consequence of mutations in either TET2 or DNMT3A [ 28 ]. Sterile inflammation also plays a role in myelodysplasia, where it is thought to contribute to disease progression [ 29 ].…”
Section: Lessons From Clonal Hematopoiesismentioning
confidence: 99%
“…The high incidence of sub-clinical CHIP poses two key questions: First, how do lesions in epigenetic control mechanisms lead to persistent, low-level clonal expansion without causing overt transformation, and second, how can mutations in genes encoding such opposing activities as methylation ( DNMT3A ) and demethylation ( TET2 ) have such similar consequences? CHIP is associated with an increased risk of atherosclerotic cardiovascular disease [ 23 ] and this has led to the identification of de-regulated inflammation as a common consequence of mutations in either TET2 or DNMT3A [ 28 ]. Sterile inflammation also plays a role in myelodysplasia, where it is thought to contribute to disease progression [ 29 ].…”
Section: Lessons From Clonal Hematopoiesismentioning
confidence: 99%
“…Additionally, M-CHIP, but not L-CHIP, represented a risk factor for coronary artery disease [ 259 ]. Other studies have also reported such a link between CHIP (with characteristics consistent with M-CHIP) and the increased risk of coronary artery disease, chronic heart failure, degenerative aortic valve stenosis, atrial fibrillation or stroke, and of autoimmune diseases and potentially osteoarthritis, and/or have aimed to better define the mechanisms of action, to improve patient management and to identify therapeutic targets that are still in their infancy as reviewed [ 243 , 251 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 ].…”
Section: Shifting Human Hsc Heterogeneity With Aging and Clonal Hemat...mentioning
confidence: 99%
“…Age-associated alterations in hematopoietic cells lead to clonal hematopoiesis which in turn can be associat-ed with the formation of the inflammatory environment and higher risk of atherosclerotic cardiovascular disease (Perner et al 2019;SĂĄnchez-Cabo and Fuster 2021). Clonal hematopoiesis is often linked with accumulating with age mutations particularly in DNMT3A, TET2, and JAK2 genes coding for DNA methyltransferase 3 alpha, Tet methylcytosine dioxygenase 2, and Janus kinase 2, respectively (Silver et al 2021;Cobo et al 2022). We suggest that mutations in these genes might shift the balance in macrophage polarization, so that increase in M1 amount leads to chronic inflammation (and atherosclerosis), whereas M2 prevalence ends up with cancer.…”
Section: Effect Of Fading Of Immune System Cells On the Atheroma Deve...mentioning
confidence: 99%